Perilaku masyarakat dalam pengelolaan dan pemanfaatan hutan rakyat : studi kasus di desa Kresnowidodo kecamatan Tegineneng kabupaten Pesawaran propinsi Lampung - Rommy Qurniati (Institut Pertanian Bogor, 2010)
Degradation in production forest in lampung Province was high. Wood crop was cut and changed with agriculture crop and also the settlement. Cultivation of wood in land that own by society with private forest (hutan rakyat) pattern in Kresnowidodo Village become one of solution for rare of this wood. According to that, need to know how behavior socialize in management and wood exploiting from private forest in Kresnowidodo Village in order to overcoming the rare of wood and development of private forestspecially in lampung Province. location have been selected in purposive method with consideration that Kresnowidodo Village have 227 ha private forest. Farmer population that have private forest are 315 family. According to Slofin method obtained 39 family as sample. The method used descriptive qualitative analysis. Community behavior in management and exploiting of private forest analysed from three aspect that are produce aspect, processing aspect and marketing aspect. The result obtained that wood production in private forest still be conducted traditionally. Farmers did not conducted management intensively yet since assuming private forest land still be fertile enough to support growth of wood crop. The exploitation of private forest still as peripheral income and used as saving or reserve of farmer income. The existance of wood industry in Kresnowidodo Village become one of farmer motivation to develop private forest. Certainty in wood production from private forest supported with efficient wood market in the village perhaps have supported for development and continuation of private forest in Kresnowidodo Village.